Konsep Kasih Sayang Orang Tua dalam Kitab Wasaya Al-Aba’ li Al-Abna’ dan Relevansinya dengan Kurikulum Berbasis Cinta - Sa'adah, Khotimatus; Hakim, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the limited research on the concept of parental affection in classical Islamic texts, despite its important role in shaping character within modern education. This study aims to examine the concept and forms of parental affection in the book Wasaya Al-Aba’ li Al-Abna’ and analyze its relevance to the Love-Based Curriculum. This research employs a qualitative approach using library research, with the primary data source derived from the work of Syaikh Muhammad Syakir and supported by relevant literature. Data were collected through documentation and analyzed using thematic content analysis. The findings reveal that parental affection in the book is presented comprehensively, encompassing spiritual guidance, moral and character development, social ethics, and discipline through daily habituation. These values are not merely emotional expressions but are implemented through structured educational guidance. Furthermore, the findings indicate that these values are aligned with the principles of the Love-Based Curriculum, particularly in fostering empathy, emotional connection, and a humanistic learning environment. This study concludes that parental affection constitutes a fundamental and holistic approach to character formation. The implications of this research include theoretical contributions to the development of affection-based Islamic education and practical recommendations for educators to integrate empathy and compassion values into the learning process. Future research is suggested to explore the empirical implementation of these values in educational settings.